2021
DOI: 10.1001/jamanetworkopen.2021.41353
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Calorie Content of Menu Items at Large Chain Restaurants After Implementation of Calorie Labels

Abstract: IMPORTANCE Calorie labeling on menus is required in US chain food establishments with 20 or more locations. This policy may encourage retailers to offer lower-calorie items, which could lead to a public health benefit by reducing customers' calorie intake from prepared foods. However, potential reformulation of restaurant menu items has not been examined since nationwide enforcement of this policy in 2018.OBJECTIVE To examine the calorie content of menu items at large chain restaurants before and after impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Our analysis includes 10 Odds ratios (OR) comparing the likelihood of an item meeting or exceeding the 2,300 mg sodium threshold are shown in Table 4. Compared to baseline, there was a non-significant increase in the overall likelihood of menu items at follow-up requiring a warning icon (OR=1.32, 95% CI=0.97, 1.79).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis includes 10 Odds ratios (OR) comparing the likelihood of an item meeting or exceeding the 2,300 mg sodium threshold are shown in Table 4. Compared to baseline, there was a non-significant increase in the overall likelihood of menu items at follow-up requiring a warning icon (OR=1.32, 95% CI=0.97, 1.79).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to informing purchasing decisions, menu labeling at chain restaurants may lead to improvements in the nutritional composition of offered menu items. In an analysis of 59 national chain restaurants between 2012-2019, Grummon et al reported that menu items newly introduced following implementation of calorie labeling, in accordance with the federal requirement, were lower in calories than items newly introduced prior to calorie labeling [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of whether labelling can elicit meaningful effects on behaviour, information on calories can enable people to accurately estimate calorie intake from drinks 45 and appears to be highly acceptable to the public. It may also lead to indirect impacts, for example by encouraging industry and supermarkets to increase the availability or promotion of lower calorie alternatives 33,46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering this context, in 2016, NYC began enforcing a sodium warning regulation. A body of research shows that warning labels on foods can increase consumer knowledge and facilitate healthier choices [ 13 ] and that improvements in the nutritional composition of chain restaurant menu items may follow menu labeling mandates [ 14 ]. This novel policy requires chain restaurants (those with 15 or more locations nationally) to display warning icons next to high-sodium menu items (containing ≥2,300 mg sodium) and post a statement explaining the icon and associated health risks [ 15 ] (S1 Fig in S1 File ) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%